Collision of lions and butterflies or mutual neglect - outside the Anglo-American domain, too? The publication and citation behaviour of economic geographers and geographical economists compared - Rolf Sternberg (Philipps-University Marburg, Department of Geography, 2013)
This paper compares the publication and citation behaviour of economic geogra- phers and geographical economists. Based on a unique data set and consciously limited to researchers in the German-speaking world, empirical analyses show more parallels than expected. Convergence of scholars from both disciplines over time can be observed, as younger papers are more similar to each other than older ones. Publication together with foreign scholars is also becoming more frequent. Joint publications of both disciplines are still a rare, but increasing phenomenon. There seems to be a cooperation dividend if the lion and the butterfly write joint articles.
Keywords: Y80; R10; 330; publications; citations; economic geography; geographical economics